2008
DOI: 10.1074/jbc.m800729200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor CAR Requires Early Growth Response 1 to Activate the Human Cytochrome P450 2B6 Gene

Abstract: The nuclear receptor CAR (constitutive active/androstane receptor) is a drug-sensing transcription factor, regulating the hepatic genes that encode various drug-metabolizing enzymes. We have now characterized the novel regulatory mechanism by which the signal molecule EGR1 (early growth response 1) determines CAR-mediated activation of the human CYP2B6 (cytochrome P450 2B6) gene. The CYP2B6 enzyme metabolizes commonly used therapeutics and also activates pro-drugs. The CAR directly binds to the distal enhancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 30 publications
1
32
2
Order By: Relevance
“…The mechanism of nuclear translocation of CAR uses various cell-signaling molecules, such as protein phosphatase 2A and extracellular signal-regulated kinase 1/2 (Yoshinari et al, 2003;Koike et al, 2007). In addition to what is observed in the cytoplasm, early growth response 1 promotes CAR to transactivate the CYP2B6 gene in HepG2 cells as effectively as that in primary hepatocytes and livers (Swales et al, 2005;Inoue and Negishi, 2008). Thus, CAR-mediated transactivation of its target genes appears to be coregulated by CAR activators and cell-signaling molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of nuclear translocation of CAR uses various cell-signaling molecules, such as protein phosphatase 2A and extracellular signal-regulated kinase 1/2 (Yoshinari et al, 2003;Koike et al, 2007). In addition to what is observed in the cytoplasm, early growth response 1 promotes CAR to transactivate the CYP2B6 gene in HepG2 cells as effectively as that in primary hepatocytes and livers (Swales et al, 2005;Inoue and Negishi, 2008). Thus, CAR-mediated transactivation of its target genes appears to be coregulated by CAR activators and cell-signaling molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocyte and cell extracts were prepared by lysis of cells with 1 Â LDS buffer (Life Technologies) with 1% beta-mercaptoethanol. Protein separation and detection were performed as described previously (Inoue and Negishi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…15 Finally, this would be in line with the finding that cotreatment with the CAR agonist TCPOBOP and PMA had an additive effect on activation of the human CYP2B6 gene in vitro. 50 The presence of putative PKC phosphorylation sites on the Rfc1 protein 11 suggested that downregulation of Rfc1-dependent MTX uptake may be due to carrier phosphorylation associated with a modified substrate affinity. However, our results indicate Resistance to MTX chemotherapy by antiepileptic drugs S Halwachs et al that cPKC activation by PB-dependent induction of the CAR signaling pathway does not result in elevated Rfc1 phosphorylation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated that the cross-talk of HNF4␣ with CAR or PXR is critical for the appropriate drug-mediated induction of major human CYP genes, such as CYP3A4 or CYP2C9 (49 -52). More recently, the important role of the proximal HNF4␣ response element in the cooperation between EGR1 and CAR for CYP2B6 induction has also been demonstrated (25). All of A, total RNA from six liver donors showing high (n ϭ 3) and low (n ϭ 3) CYP2B6 expression was purified, and the mRNA levels of CYP2B6, C/EBP␣, HNF4␣, and CAR were determined by real-time quantitative RT-PCR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion assays delineate the OA-responsive activity to a proximal 50 bp (Ϫ217 to Ϫ268 bp) sequence in the CYP2B6 promoter (24,25). In this OA-responsive module, EGR1 (early growth response 1) and HNF4␣ (hepatocyte nuclear factor 4␣) bind and determine the CAR-mediated induction of the human CYP2B6 gene.…”
mentioning
confidence: 99%